A Curator-General: N. N. Golovin and the Hoover Institution for War, Revolution, and Peace. (1st October 2020) - Shmelev, Anatol
ABSTRACT: This article describes the contributions of General Nikolai Nikolaevich Golovin (1875–1944) to the fields of bibliography and archives. As an agent and later the Russian military curator for the Hoover War Library, Golovin helped acquire a large number of singularly important collections for the Hoover Institution, laying the groundwork for its stellar Russian holdings. He also created a number of bibliographic guides, especially to articles in the Russian émigré periodical press, that continue to retain their significance for researchers.